Key factors for stable retention of fluorophores and labeled biomolecules in droplet-based microfluidics - Janiesch, Jan-Willi; Weiss, Marian; Kannenberg, Gerri; Platzman, Ilia; Spatz, Joachim P. (Analytical chemistry, 2015)
Water-in-oil emulsion droplets created in droplet-based microfluidic devices have been tested and used recently as well-defined picoliter-sized 3D compartments for various biochemical and biomedical applications. In many of these applications, fluorescence measurements are applied to reveal the protein content, spatial distribution, and dynamics in the droplets. However, emulsion droplets do not always provide entirely sealed compartments, and partitioning of dyes or labeled molecules to the oil phase is frequently observed. Therefore, stable molecular retention in the droplets represents a challenge, and many physical and chemical key factors of microfluidic system components have to be considered. In this study, we investigated the retention of 12 commonly used water-soluble dyes in droplets having six different aqueous phase conditions. We demonstrate that the physicochemical properties of the dyes have a major influence on the retention level. In particular, hydrophilicity has a strong influence on retention, with highly hydrophilic dyes (LogD < −7) showing stable, buffer/medium independent retention. In the case of less hydrophilic dyes, we showed that retention can be improved by adjusting the surfactants physical properties, such as geometry, length, and concentration. Furthermore, we analyzed the retention stability of labeled biomolecules such as antibodies, streptavidin, and tubulin proteins and showed that stable retention can be strongly dependent on dye and surfactants selection.